Allergies dermatitis, rhinitis, and asthma - Javier, Angelo Dave C.; Lagunzad, Juan Paolo DLC.; Gloria, Cesar Joseph (Quezon City Milflores Publishing, 2010)
About half of all the people in the world suffer from some form of allergies that harms their health, quality of life, and productivity. In this booklet, leading medical experts discuss the three most common allergic diseases--Atopic dermatitis, allergic rhinitis, and allergic asthma--and the best ways to diagnose and treat these conditions.
Keywords: Allergy -- Treatment; Allergy -- Prevention; Skin -- Inflammation -- Treatment; Skin -- Inflammation -- Prevention; Rhinitis -- Treatment; Rhinitis -- Prevention; Asthma -- Treatment; Asthma -- Prevention